Penerapan Strategi Metakognitif Dalam Pembelajaran Bahasa Indonesia Siswa Sekolah Dasar - Ikawati, Erna; Kartono, Azwir; Hutagalung, Nenny Triana (Jurnal Hata Poda, 2023)
Every learning process must have the right strategy to apply, Strategylearning a language is a special way that learners improvelanguage skills. This article discusses the importance of language learning strategiesmetacognitive in the context of elementary school education in terms of the studylibrary. Metacognition involves understanding and monitoring the learning process.Implementation of metacognitive strategies for elementary school students in learning Indonesianis expected to be able to improve students' learning strategies to focus on lessons,plan, monitor and evaluate language learning.Keywords: Metacognitive Strategy, Indonesian Language Learning, Elementary School